Domino Flap Using Bilobed Flap for Large Scapular Flap Donor Site: A Case Report - Meirizal, Meirizal; Irfantian, Ardicho; Huwaidi, A. Faiz; Lo, Agung Susilo (Archives of Plastic Surgery, 2025)
Scapular flaps are favored for large soft tissue defects, but with a high risk of shoulder contracture. This case report presents a novel application of a bilobed flap technique to cover the donor site after harvesting a 23-cm scapular flap. The patient was a 25-year-old male with a right-hand open degloving injury measuring 25 × 22 cm. The scapular flap was planned to cover the soft tissue defect, and the bilobed flap was used to close the donor site. After 6 months, the left shoulder showed full range of motion, and the scapular flap was viable with good right-hand function. This case introduces the largest bilobed flap used to date. The report emphasizes two main advantages, it prevents shoulder contracture and allows surgeons to exceed the traditionally recommended flap size with minimal donor site morbidity. The large bilobed flap has proven effective in closing donor site defects following scapular flap harvest, demonstrating satisfactory outcomes. Additionally, this technique can be utilized to address other donor site defects.
Keywords: bilobed flap; scapular flap; reconstruction